Edulabs for the integration of technologies in Basic Education – monitoring the AGIRE project - Pombo, Lúcia (2016)
The AGIRE project is a partnership between the University of Aveiro, a consortium comprising 26 companies related to teaching and learning, and one School Grouping, with the financial support of QREN. The project is embedded into the Edulab concept (school laboratories with technological equipment, as tablets, laptops, whiteboards, and educational materials such as eBooks and learning platforms) to promote the adoption of innovative teaching practices. The project stems from identified contextual needs and aims to monitor the project implementation within an interventional perspective, concerning educational innovation with the use of digital technologies. The goal is to promote teachers‟ and students‟ digital literacy, by developing Teacher Training Courses (TTC) and taking advantage from the school technology environment on a pedagogical level. After attending a short-term (15 hours) technological TTC, a 64-hour TTC involving 13 teachers of Basic Education during the current school year is being conducted. The TTC, developed in a blended learning environment, follows the flipped classroom methodology comprising autonomous tasks for consulting multimedia resources at a distance and face-to-face sessions for discussion, reflection and collaborative work. This fits into a design-based methodology (Parker, 2011), allowing the analysis of the intervention outcomes and it‟s successively refinement towards a solution, following the phases: i) Analyze the problem; ii) Design and develop potential solutions; iii) Implement and evaluate; and iv) Reflect and report. A set of data collection instruments developed under this project allowed its monitoring, as well as the redefinition of the TTC and its previewed activities. For example, the questionnaire on the trainee teachers‟ digital literacy, the grid to monitor the strategies implemented in classrooms, as well as the autonomous work tasks allowed each teacher to position its practice at the level of technology integration and to raise his/her expectations towards the educational technologies.